Optimum conditions in the use of young inflorescence for transgenic plant regeneration of rice (Oryza sativa L.) - Aldemita, R. R. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2001)
Current breeding in rice focuses on developing new plant type (NPT) lines with long panicles and strong and thick culms to support more seeds - characteristics that make NPT lines highly prone to the attack of pests. Genetic engineering is now geared toward improving NPT lines to increase their resistance to pests and diseases. Conditions for A. tumefaciens-mediated transformation of NPT elite lines had been optimized by considering the explant, selection conditions and the different artificial media used. Transgenic plants were obtained from calli derived from mature seeds and young inflorescence using the developed protocol. Transgenic plants were grown to maturity, and ploymerase chain reaction and Southern blot analyses confirmed the presence of the transgene in the transformed NPT lines. Ours is the first report of successful genetic transformation of young rice inflorescence.